1999
DOI: 10.1021/bi982255j
|View full text |Cite
|
Sign up to set email alerts
|

N-Acylglycine Amidation:  Implications for the Biosynthesis of Fatty Acid Primary Amides

Abstract: Bifunctional peptidylglycine alpha-amidating enzyme (alpha-AE) catalyzes the O2-dependent conversion of C-terminal glycine-extended prohormones to the active, C-terminal alpha-amidated peptide and glyoxylate. We show that alpha-AE will also catalyze the oxidative cleavage of N-acylglycines, from N-formylglycine to N-arachidonoylglycine. N-Formylglycine is the smallest amide substrate yet reported for alpha-AE. The (V/K)app for N-acylglycine amidation varies approximately 1000-fold, with the (V/K)app increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 74 publications
5
68
1
Order By: Relevance
“…The levels of tridecanamide produced from N -tridecanoylethanolamine were higher than those produced by tridecanoate in the SCP cells. The differences in overall production of tridecanamide between preference for longer acyl chain substrates ( 34,35 ). The higher PFAM 48 /PFAM 12 ratio in the N 18 TG 2 cells relative to the SCP cells refl ects a greater net rate of PFAM biosynthesis in the N 18 TG 2 cells, a lower net rate of PFAM degradation in the N 18 TG 2 cells, or a combination of both.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels of tridecanamide produced from N -tridecanoylethanolamine were higher than those produced by tridecanoate in the SCP cells. The differences in overall production of tridecanamide between preference for longer acyl chain substrates ( 34,35 ). The higher PFAM 48 /PFAM 12 ratio in the N 18 TG 2 cells relative to the SCP cells refl ects a greater net rate of PFAM biosynthesis in the N 18 TG 2 cells, a lower net rate of PFAM degradation in the N 18 TG 2 cells, or a combination of both.…”
Section: Discussionmentioning
confidence: 99%
“…Less is defi nitively known about PFAM biosynthesis. One proposed route is the ammonolysis of fatty acyl-CoA thioesters ( 33 ), whereas a second proposed route involves the oxidative cleavage of N -fatty acylglycines ( 34,35 ). Mouse neuroblastoma N 18 TG 2 cells are known to produce oleamide ( 36 ) and, thus, must possess the enzymatic machinery necessary for oleamide biosynthesis.…”
mentioning
confidence: 99%
“…Milman et al [71] recently isolated and characterized N-arachidonoyl-L-serine from bovine brain and showed that this novel N-fatty acylserine had vasodilatory properties. We have proposed that the N-fatty acylglycines are biosynthetic precursors to the PFAMs, being oxidatively cleaved to the corresponding PFAM and glyoxylate in a reaction catalyzed by peptidylglycine α-amidating monooxygenase (PAM) [72]. Recent evidence suggests that the N-fatty acylglycines may serve as more than simple PFAM pathway intermediates and may have independent functions: N-oleoylglycine regulates body temperature and locomotion [73], Narachidonoyltaurine activates TRPV1 and TRPV4 calcium channels of the kidney [74], Narachidonoylglycine is an endogenous ligand for the orphan GPR18 receptor, [75], Narachidonoyl-γ-aminobutyric acid is analgesic [76], and N-arachidonoylglycine is analgesic, and inhibits FAAH [77] and the GLYT2a glycine transporter [78].…”
Section: N-acylamino Acidsmentioning
confidence: 99%
“…FAAH will hydrolyze the N-acyltaurines and N-arachidonoylglycine to the corresponding fatty acid and amino acid [33,76], but the other N-acylamino acids are not degraded by FAAH [77]. We have shown that N-acylglycines are biosynthetic precursors to the PFAMs using purified PAM [72] and in PAM-expressing neuroblastoma cells [93][73] [92][E1]. Marnett and co-workers have found that the N-arachidonoylamino acids are substrates for lipoxygenase and cyclooxygenase in vitro [94,95], pointing either to a mechanism for the inactivation of the N-arachidonoylamino acids or for the formation of other bioactive, oxidized amino acid conjugates.…”
Section: N-acylamino Acidsmentioning
confidence: 99%
“…N-dealkylation, O-dealkylation and sulfoxidation reactions are shown [53]. (B) PAM catalyzes the oxidative cleavage of N-acylglycines ranging in length from N-formyl to N-arachidonyl [54,55]; the formation of oleamide, a potent sleep-inducing agent, is shown [57,58]. (C) PAM converts nicotinuric acid into nicotinamide via a hydroxyglycine intermediate, suggesting a role for PAM in the formation of many nonpeptide primary amides [56].…”
Section: Review Articlementioning
confidence: 99%